ADOPSI INOVASI PROGRAM PEMBANGUNAN AREAL MODEL HUTAN RAKYAT DI DESA BAKAL DALAM KECAMATAN TALO KABUPATEN BENGKULU SELATAN - Asriani, Putri Suci (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
The succes of community forest areal model development program in the location of Baka/ Da/am village, T810 subdistrict, South of Bengkulu district very depend on wffh efective or inefective adoption-inovation process to this program. In addition to obsetVed from positif perseption as indicated with direct by participant farmers in this program, low or high personal motivation partiCipant farmers to this program, and rank of this participation.